Neurogenin 2 controls cortical neuron migration through regulation of Rnd2 - Heng, Julian Ik-Tsen; Nguyen, Laurent; Castro, Diogo S.; Zimmer, Céline; Wildner, Hendrik; Armant, Olivier; Skowronska-Krawczyk, Dorota; Bedogni, Francesco; Matter, Jean-Marc; Hevner, Robert; Guillemot, François (Nature, 2008)
Neuronal migration: neurogenin 2 acts via Rnd2 Proneural transcription factors, such as neurogenin 2, are thought to control the expression of many genes during brain development to promote both the differentiation of neurons and their migration to their final locations in the cerebral cortex. A new study reveals that overexpression of a single target of neurogenin 2, Rnd2, can restore the neuronal migration defects of Neuogenin2-depleted neurons. Rnd2 is thus an atypical member of the Rho family of small GTP-ases, which regulate actin cytoskeleton dynamics, with its activity regulated at the gene transcription level, rather than by the usual post-translational GTP/GDP cycle. A study reveals that overexpression of a single target of neurogenin 2, Rnd2 , can restore the neuronal migration defects of neurogenin 2-depleted neurons. Rnd2 is thus an atypical member of the Rho family of small GTP-ases, which regulate actin cytoskeleton dynamics, with its activity regulated at the gene transcription level, rather than by the usual post-translational GTP/GDP cycle. Motility is a universal property of newly generated neurons. How cell migration is coordinately regulated with other aspects of neuron production is not well understood. Here we show that the proneural protein neurogenin 2 (Neurog2), which controls neurogenesis in the embryonic cerebral cortex 1 , 2 , directly induces the expression of the small GTP-binding protein Rnd2 (ref. 3 ) in newly generated mouse cortical neurons before they initiate migration. Rnd2 silencing leads to a defect in radial migration of cortical neurons similar to that observed when the Neurog2 gene is deleted. Remarkably, restoring Rnd2 expression in Neurog2 -mutant neurons is sufficient to rescue their ability to migrate. Our results identify Rnd2 as a novel essential regulator of neuronal migration in the cerebral cortex and demonstrate that Rnd2 is a major effector of Neurog2 function in the promotion of migration. Thus, a proneural protein controls the complex cellular behaviour of cell migration through a remarkably direct pathway involving the transcriptional activation of a small GTP-binding protein.